PENGARUH KECERDASAN KEROHANIAN, LITERASI DIGITAL, DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMP MUHAMMADIYAH SE-KABUPATEN CIANJUR - Sunarya, Ayi; Suryadi, Ahmad (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
This study aims to analyze the influence of spiritual intelligence, digital literacy, and work motivation on the performance of teachers at Muhammadiyah junior high schools across Cianjur Regency. The research employs a quantitative approach using the Structural Equation Modeling (SEM) method based on SmartPLS 3.0, involving 100 teacher respondents from various Muhammadiyah junior high schools during the 2024/2025 academic year. The analysis results indicate that spiritual intelligence has a significantly positive effect on teachers’ work motivation (t-statistic = 4.728, p < 0.05), and digital literacy also has a significant positive effect on work motivation (t = 3.621, p < 0.05). Moreover, spiritual intelligence has a direct impact on teacher performance (t = 2.843), as does digital literacy (t = 2.645), while work motivation has a highly significant effect on teacher performance (t = 5.029). Work motivation is also proven to mediate the relationship between spiritual intelligence and teacher performance (t = 3.112) as well as between digital literacy and teacher performance (t = 2.978). The research model shows a coefficient of determination (R²) of 0.678 for the teacher performance variable, indicating that 67.8% of the variation in teacher performance can be explained by the combined effects of spiritual intelligence, digital literacy, and work motivation. These findings affirm that the integration of spiritual values, digital literacy competence, and increased work motivation is a key strategy to strengthen teacher professionalism and build a value-based, technology-oriented, and highly dedicated educational ecosystem within the framework of progressive Islamic education.